Large-Scale and High-Resolution Patterning Based on the Intense Pulsed Light Transfer of Inkjet-Printed Light-Emitting Materials - Lee, Youngwoo; Han, Young Joon; Cho, Kuk Young; Cho, Kwan Hyun; Jeong, Yong-Cheol (Macromolecular research, 2021)
In this study, we present a hybrid fabrication method using the intense pulsed light transfer of inkjet-printed light-emitting materials for large-scale and high-resolution patterning. The surface morphology of inkjet-printed thin film is improved by introducing a newly synthesized non-sublimable additive to the conventional light-emitting materials. Finally, we also demonstrate successful photothermal transfer from a light-to-heat-conversion donor substrate to the target device substrate with a 1000 PPI resolution pattern.